Developing an Innovative Energy Efficiency Financing Mechanism in China - World Bank (World Bank, Washington, DC, 2017)
The policy environment in China is conducive to green energy financing.The policy environment in China is conducive to green energy financing. TheGovernment of China (GoC) is undertaking one of the most aggressive energy efficiency (EE) and renewable energy (RE) campaigns in the world.For the 13th FYP (2016–2020), the GoC plans to adopt a total energyconsumption cap and a coal consumption cap, in addition to 15 percent energy intensity reduction target. China currently has the world’s largest installed RE capacity, with 130 gigawatts (GW) of wind and 43 GW of solar photo voltaic (PV) by the end of 2015. REcurrently accounts for 11 percent of total primary energy; and the GoC plans for non-fossilfuel to reach 15 percent by 2020 and 20 percent by 2030. This study aims to provide inputs to the Chinese government’s envisioned Green Fund. Since the closure of the energy efficiency rewards funds in early 2015, the NationalDevelopment and Reform Commission (NDRC) Environmental Protection and Resource Conservation Department is interested in setting up an energy efficiency fund with government budget to maximize its leverage of commercial financing for energy efficiency investments.The market demand for green energy financing is huge for the 13th FYP.The lion’s share of the green energy investments needs will come from commercial financing. However, the banking sector’s uptake of green financing remains low relative to the huge investment needs, and many EE/RE enterprises continue to face difficulties inaccess to financing. International and domestic experiences offer a wealth of experience and lessons learned. This study reviewed a wide range of green energy financing mechanisms from internationalexperience, including credit lines, risk guarantees, green funds, green banks, utility demandside management (DSM) funds, utility on-bill financing, ESCO financing and leasing, etc.The study found that a Green Energy Fund, with a dedicated team and mandate to invest inthe green energy market, has a higher chance to overcome the above mentioned barriers to increase financing flow to the targeted market and underserved clients, and also has a highleverage of public funds. The study also found that generating sufficient deal flows is a major challenge to green energy financing mechanisms. This study also examined in details on international experience of setting up a green energy fund.This study also reviewed Chinese experience in government funds, with the intent to learn thestructure, financing instruments, and lessons from existing government funds in China. Most of the existing government funds aim to promote new technologies, and very few are targeted at green energy market to date. This study also reviewed relevant laws, policies and regulations issued by central government agencies. This study conducted preliminary design of a potential Green Energy and Emission Reduction Fund: The preliminary design includes strategic focus, targeted market, financingsources, fund structure, fund scale and leveraging ratio, financial products, eligibility criteria,and exit strategy.